Trends in car use, travel demand and policy thinking - Phil Goodwin (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper discusses the main trends of car use and travel demand, as well as changes in policy responses and attitudes to managing the growth in urban traffic. It highlights the importance of orienting transport policies towards broader objectives beyond efficiency of congestion relief. Such a comprehensive set of objectives would include improvements in health, air quality, active travel activity, human well-being, as well as accessibility and fairness.
Keywords: 330; Verkehrsverhalten; Stadtverkehr; Lebensqualität; Faktorenanalyse